Healing of Traumatic Ulcer Using Hyaluronic Acid Gel: A Case Report - Citra Saka Gama Diarum; Shoimah Alfa Makmur; Putri Kusuma Wardani Mahendra (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2026)
Traumatic ulcers are ulcerative lesions caused by mechanical, electrical, or chemical trauma. In children, the prevalence of oral ulcers reaches approximately 9%. Topical gel is commonly chosen as the first-line treatment for ulcers, due to their effectiveness in protecting the lesion and alleviating pain caused by friction with surrounding tissues. Topical gel formulations containing hyaluronic acid as the active ingredient have demonstrated significant therapeutic benefits in the management of oral ulcers. It contributes to the healing process by maintaining adequate moisture at the lesion, facilitating the initiation of the inflammatory and proliferative phases, and ultimately promoting faster tissue regeneration and wound closure. This article presents the management of a traumatic ulcer in a 3-year-old child resulting from an accident. The ulcer was located in the anterior maxillary region and was accompanied by the avulsion of teeth 51 and 61. The lesion was treated with topical hyaluronic acid gel. The treatment spanned over a period of two months, during which new gingival tissue developed, covering the exposed alveolar bone and socket following the trauma.In cases involving extensive traumatic ulcers, such as the present case, the application of hyaluronic acid gel has demonstrated efficacy in facilitating tissue regeneration. The selection of an appropriate topical therapeutic agent is particularly important in pediatric patients to ensure optimal healing outcomes, patient comfort, and adequate nutritional intake during recovery. Hyaluronic acid gel offers a cooling and tasteless upon application, rendering it a well-tolerated and effective option for the management of ulcerative lesions in children.